Prognostic Impact of Platelet-Large Cell Ratio In Myelodysplastic Syndromes - Chen, Qiuni; Chen, Yue; Zhang, Yijing; Zhang, Lijuan; Chen, Kankan; He, Zhengmei; Wang, Chunling; Yu, Liang (Frontiers in Oncology, 2022)
Background: The myelodysplastic syndromes (MDS) are a very heterogeneous group of myeloid disorders with high prevalence and risk of developing acute myeloid leukemia (AML). The more accurate risk stratification can provide better guidance of treatment. platelet-large cell ratio (P-LCR) is a parameter reported in complete blood cell count tests, and was associated with many diseases, but its role in MDS is not clear. Purposes: This study aims to explore the impact of P-LCR on the prognosis of patients with MDS, which is of great significance for clinical treatment. Methods: In the retrospective study, 122 newly diagnosed MDS patients were enrolled. We used a bio-informatics tool X-tile to define a P-LCR threshold of 36.7% to predict prognosis. Patients were divided into P-LCRlow and P-LCRhigh groups, and their characteristics were compared between the two groups. Results: Results show that P-LCRlow was associated with worse OS than P-LCRhigh patients (median OS, 18.53 months versus 25.77 months, p=0.0057). But there were no statistical differences in PFS between the two groups (p= 0.2001). Results of univariate and multivariate COX proportional hazard analyses adjusted for gender, bone marrow blasts level, platelet count and IPSS scores showed P-LCR was useful in the evaluation of PFS (HR 0.212, 95%CI 0.064-0.702, p=0.011) and OS of MDS (HR 0.464, 95%CI 0.284-0.757, p=0.002). Conclusion: This study was the first report showing that P-LCR would be a simple and immediately available biomarker for predicting the prognosis of MDS. Keywords: Myelodysplastic syndromes (MDS); platelet-large cell ratio (P-LCR); survival; prognosis; biomarker